2005
DOI: 10.1002/ccd.20262
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison between Inoue balloon and metallic commissurotome in the treatment of rheumatic mitral stenosis: Immediate results and 6‐month and 3‐year follow‐up

Abstract: The metallic commissurotome (MC) technique is a cheaper alternative to the Inoue balloon (IB) technique for percutaneous mitral valvuloplasty (PMV). There are no randomized trials comparing these techniques with longer follow-up of the patients. The objective of this study was to compare the immediate results and short- and medium-term follow-up of PMV using either the IB or the MC technique. Fifty patients with rheumatic mitral stenosis were randomly assigned to PMV using the IB (n = 27) or the MC (n = 23) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Regarding MR, one patient in each group had to go for emergency MVR because of AML tear, in our series. Other authors also report a similar incidence of MR requiring MVR [18, 19, 29].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Regarding MR, one patient in each group had to go for emergency MVR because of AML tear, in our series. Other authors also report a similar incidence of MR requiring MVR [18, 19, 29].…”
Section: Discussionmentioning
confidence: 53%
“…In a nonrandomized comparison, Mittal et al [30], found that PMMC group ( n = 127) had a higher gain in valve area compared with Inoue ( n = 350) technique, (126% vs. 111.4% ( P < 0.05). Also in the series by Guerios et al [29], PMMC produced a larger postvalvuloplasty valve area (1.98 vs. 2.17 cm 2 , P = 0.04), immediately after the procedure.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A low rate of complication with significant clinical and hemodynamic improvement is expected in the short and long term 4 . In successful procedures, the mitral valve area usually doubles, and the transvalvular gradient decreases by 50% to 60% immediately after the procedure 3,5 .…”
Section: Resultsmentioning
confidence: 99%